Characteristics of Double-J Stent Encrustations and Factors Associated with their Development - Huang, Jian; Wu, Weizhou; Zhang, Shike; Huang, Yapeng; Zeng, Tao; An, Lingyue; Liang, Yeping; Huang, Jinkun; Tiselius, Hans-Göran; Zeng, Guohua; Wu, Wenqi (Urology Journal, 2021)
Purpose: To evaluate the chemical composition of double-J stent encrustation and to assess risk factors associated with their development. Materials and Methods: Patients who had double-J stents removed between July 2016 and June 2017 were recruited for this study prospectively. The clinical features of the patients were recorded and the composition of encrustation material was analyzed by infrared spectroscopy. Results: Encrustments from a total of 372 double-J stents were collected. The mean age of patients was 50.4±13.1 years and deposits possible to analyze were obtained from 228 males (61.3%) and 144 females (38.7%). Calcium oxalate monohydrate was the most common constituent of stone and encrustments. The encrustation rate of vesical coils was significantly higher than that of renal coils (P<0.001). There was no significant difference in chemical composition between stone and encrustation regarding renal (P=0.086) and vesical coils (P=0.072). The only predictive risk factor for the development of encrustation on double-J stents was indwelling time. This phenomenon was observed in both renal (P<0.001) and vesical coils (P=0.021). Interestingly, patient with chronic kidney disease (CKD) was associated with less risk of encrustation on both renal (P<0.001) and vesical coils (P=0.001). Conclusion: The chemical composition of double-J stent encrustation was the same as the urinary stone. The prevention strategy for stone composition is also suitable for the prevention of encrustation of double-J stent. The only predictive factor for double-J stent encrustation was the indwelling time. CKD patient was shown to be less at risk for the development of encrustation.